The Role of the Land Office in Efforts to Increase Public Awareness Regarding Complete Systematic Land Registration - Agustin, Vany; Hadi Prayitno, Ahmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to find out and analyze the implementation of complete systematic land registration in Cirebon Regency, to find out and analyze the role of the land office in efforts to increase public awareness regarding complete systematic land registration in Cirebon Regency, and to find out and analyze obstacles and solutions in efforts to increase public awareness regarding complete systematic land registration. The research approach used in this thesis is an empirical juridical legal research method. This research specification uses descriptive analysis. The type of data used in this research is primary data through field studies in the form of practical experience and opinions of research subjects about everything related to this research. as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and studying documents or library materials. The data analysis method used in analyzing the data is qualitative analysis. The research results show that there is still a high number of people who have not registered their land. Efforts that ATR/BPN can make at the Cirebon Regency Land Office in implementing the Complete Systematic Land Registration Program are to collaborate with the community in speeding up the Complete Systematic Land Registration program. It is hoped that for future PTSL activities, they will carry out comprehensive outreach activities and explain them in detail and clearly so that public awareness can be created to register their land through PTSL activities. Keywords: Certificate; Community; Land.